Pengujian Galur Kedelai di Lahan Pasang Surut - M. Sabran; Eddy William; M. Saleh (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
Testing of soybean genotypes were conducted at six locations of tidal swampland; in dry season of 1999/2000. Eight genotypes and two checks varieties i.e. Wilis and Slamet were evaluated for their yield potential. The experiment was using Randomized Completely Block Design with four replications. The result showed that yield of two genotypes, MSC 9/12-D-4 and MSC 9243-D-3, were higher and relatively stable compared to Wilis and Slamet. Key words Soybean, Tidal swampland